Analysis of Factors Influencing Pregnant Women's Participation HIV Screening in Indonesia - Nofa Anggraini; Shilvah Susilawati; Deviyana Nuraini; Desi Davia; Debby Hanna Rachmawati; Nurlaela Srifatonah; Annisa Dewita Putri; Siti Herti Nurjanah (Postgraduate, University of Mataram, 2024)
Indonesia is the third largest contributor of HIV/AIDS sufferers in Asia Pacific, after India and China. Several factors that can influence HIV screening in pregnant women include education, knowledge, attitudes about HIV screening, family support and support from health workers. This study aims to analyze the factors that influence the participation of pregnant women in HIV screening in Indonesia in 2024. This study uses a quantitative analysis method with a cross-sectional design. The research sample was 35 respondents in the first trimester of pregnancy using a purposive sampling technique. The research instrument used a questionnaire. The data used is primary data analyzed using the chi square test. The results of the univariate analysis showed that 62.90% of pregnant women underwent HIV screening, with a high level of education of 58.4%, good knowledge of 56.70%, positive attitudes of 58.00%, family support of 55.1%, and support from health workers of 55.90%. Pregnant women are expected to be able to actively seek information related to HIV screening other than from health workers or from various media so that they can have high participation in participating in the implementation of HIV screening examinations as an effort to detect HIV early.